EFFECT OF LONG TERM ADMINISTRATION OF ROCKET (Eruca sativa) ON SOME CYTOGENETIC PARAMETERS IN WHITE MICE - Ilham A. Khalaf (Mesopotamia Journal of Agriculture)
The effect of long administration of rocket (J) alternatively with cyclophosphamide (Cp) on some cytogenetic parameters in white mice bone marrow cells was studied , these inlcluded mitotic index (MI) , micronuclei (Mn) formation , and chromosomal aberrations (Ch. ab.) . In addition the effect was studied on germ cell (Sperms) by scoring the number of sperm-head abnormalities and type of abnormalities . Results indicated that Cp reduced the MI by 55 % of the normal value (6.84) , while treatment of rocket with the drug (J+Cp) restored 85.5 % (5.85) of the normal value , followed by (Cp/J) restored 83.3 % (5.7) and the treatment (J/Cp) restored the lowest level 71.5 % (4.89) . Cp raised the Mn to 18.16 which is (17) times the natural value , administration of rocket with the drug simultaneously reduced the number to 6.02 , the best treatment was (Cp/J) as the number lowered to (5.860 , then the treatment J/Cp (6.76) , all of them were higher than the negative control with significant difference (P<0.01) . Cp increased the number of Ch. ab. To about 10.5 times the natural value (1.62) , but the different treatments lowered the aberrations with significant differences compared to the positive control (P<0.01) , and the best was (J+Cp) treatment as the number reduced to 3.25 . Cp increased the number of abnormal sperms to about (18) times the natural baseline (1.15) , different treatments (mentioned above ) were able to reduce the sperm-head abnormalities to levels differ from the positive control significantly (P<0.01) . The best treatment was giving the animals rocket and drug simultaneously , as the number lowered to 3.98 , followed by Cp/J treatment (6.65) , then J/Cp treatment (7.21) , all those were higher than the negative control with significant differences (P<0.01) , the types of abnormalities were affected similarly .